Christmastime is here! - Weiss, Ellen, 1949-; S.I. Artists (Group) (Pleasantville, NY : Reader's Digest Children's Books, 2008)
Youngsters may lift the flaps to see what is happening as children get ready for the holiday season by decorating the tree, visiting Santa at the toy store, and playing outside in the snow as Santa prepares for his annual journey. On board pages.
Cover title.
On board pages.
At head of title: Fisher-Price.
"Over 50 fun flaps to lift."
Keywords: Christmas stories; Stories in rhyme; Lift-the-flap books; Toy and movable books; Board books